2016
DOI: 10.1097/spc.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction after radical prostatectomy

Abstract: Purpose of review This review will discuss erectile dysfunction (ED) in prostate cancer patients following radical prostatectomy (RP). It will focus on the prevalence and current treatments for ED as well as the emotional impact of ED and the current psychosocial interventions designed to help patients cope with this side effect. Recent findings While there is a large discrepancy in prevalence rates of ED after RP, several recent studies have cited rates as high as 85%. The concept of “penile rehabilitation”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 50 publications
0
21
0
2
Order By: Relevance
“…Researchers have identified that surgery negatively affects sexual function causing a significant impact in the social domain regarding the evaluation of post-RP QoL 15 . Another study also reinforces this finding by pointing out that the impact on erectile dysfunction goes beyond the physical aspect and affects psychological and relationship aspects 20 .…”
Section: Discussionmentioning
confidence: 72%
“…Researchers have identified that surgery negatively affects sexual function causing a significant impact in the social domain regarding the evaluation of post-RP QoL 15 . Another study also reinforces this finding by pointing out that the impact on erectile dysfunction goes beyond the physical aspect and affects psychological and relationship aspects 20 .…”
Section: Discussionmentioning
confidence: 72%
“…In various randomized, multicenter, prospective trials, in comparison to placebo, PDE5 inhibitors significantly improved all primary endpoints in patients coping with this side effect of surgical intervention for prostate cancer. Since, under conditions of sexual stimulation, the pro-erectile effects of PDE5 inhibitors are dependent upon the unimpaired function of cavernous nerves (releasing the gaseous neurotransmitter NO) innervating the vascular and non-vascular penile smooth musculature, the treatment effect is mediocre to poor in patients who had undergone non-nerve sparing pelvic surgeries [15]. This is well in accordance with the results from a recent meta-analysis indicating that the placebo effect shows a tendency to be much more pronounced among subjects with ED associated with post-traumatic stress disorder (for example, following pelvic/prostatectomy surgery) with almost no significant differences between the treatment effects exerted by placebo and PDE5 inhibitors [16].…”
Section: Recent Pde5 Inhibitors In the Treatment Of Erectile Dysfunctionmentioning
confidence: 99%
“…Prostate cancer is the second leading cause of cancer-related death in men worldwide [1, 2]. Erectile dysfunction (ED) administered by injury of cavernous nerve is a significant problem following prostate cancer surgery, which seriously affects the quality of life of patients [35]. Adipose tissue-derived stem cells (ADSCs) has significant treatment effect for ED in diabetics, post-prostatectomy patients, and those with peyronie’s disease [6, 7].…”
Section: Introductionmentioning
confidence: 99%